The Effect Of Good Corporate Governance, Leverage, Profitability And Company Size On The Value Of Manufacturing Companies In The Food And Beverage Sub-Sector Listed On The Indonesia Stock Exchange In 2021-2023 - Dwie Tirta Kencana; Nurul Kurnia (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of Good Corporate Governance (GCG), leverage, profitability, and company size on the value of manufacturing companies in the food and beverage subsector listed on the Indonesia Stock Exchange (IDX) in the period 2021-2023. This research examines the influence of several independent variables, including Good Corporate Governance (GCG), leverage, profitability, and firm size, on firm value. The study utilizes secondary data sourced from company financial statements. The data were analyzed using panel data regression to assess the relationship between these variables and firm value. The findings reveal that GCG, leverage, profitability, and firm size significantly impact the value of the company. These findings contribute to the literature related to company value and can be a reference for company management and stakeholders in making strategic decisions to increase company value.